Body size, brain size, and sexual dimorphism in Homo naledi from the Dinaledi Chamber. Issue 111 (October 2017) - Garvin, Heather M.; Elliott, Marina C.; Delezene, Lucas K.; Hawks, John; Churchill, Steven E.; Berger, Lee R.; Holliday, Trenton W.
Abstract: Homo erectus and later humans have enlarged body sizes, reduced sexual dimorphism, elongated lower limbs, and increased encephalization compared to Australopithecus, together suggesting a distinct ecological pattern. The mosaic expression of such features in early Homo, including Homo habilis, Homo rudolfensis, and some early H. erectus, suggests that these traits do not constitute an integrated package. We examined the evidence for body mass, stature, limb proportions, body size and dental size dimorphism, and absolute and relative brain size in Homo naledi as represented in the Dinaledi Chamber sample. H. naledi stature and body mass are low compared to reported values for H. erectus, with the exception of some of the smaller bodied Dmanisi H. erectus specimens, and overlap with larger Australopithecus and early Homo estimates . H. naledi endocranial volumes (465–560 cc) and estimates of encephalization quotient are also similar to Australopithecus and low compared to all Homo specimens, with the exception of Homo floresiensis (LB1) and the smallest Dmanisi H. erectus specimen (D4500). Unlike Australopithecus, but similar to derived members of genus Homo, the Dinaledi assemblage of H. naledi exhibits both low levels of body mass and dental size variation, with an estimated body mass index of sexual dimorphism less than 20%, and appears to have an elongated lower limb. Thus, the H. naledi bauplan combines features not typically seen in Homo species (e.g., small brains and bodies) with those characteristic of H. erectus and more recent Homo species (e.g., reduced mass dimorphism, elongated lower limb).